PENGARUH STRATEGI PEMBELAJARAN CARD SORT DISERTAI MIND MAPPING HASIL BELAJAR BIOLOGI SISWA SMA BANYUDONO TAHUN PELAJARAN 2011/2012 - MP, Feriana Solikati; Santosa, Slamet; Ariyanto, Joko (Pendidikan Biologi, 2012)
ABSTRACT ? Aims of this research are to know the influence of  Card Sort With Mind Mapping  learning strategies toward student?s  achievement in studying biology of  SMA N Banyudono Boyolali. This research was quasi experiment research using quantitative approach. The research was designed using posttest only randomized control group by using the experimental classes (application of Card Sort with Mind Mapping  strategy) and control classes (conventional learning). Population studies are all students of SMA N Banyudono Boyolali  in academic year 2011/2012. Sampling techniques with cluster random sampling, so chosen XI IPA 1 as the experiment class and XI IPA 2 as the control class. Data was collected using questionnaire, essay test, observation sheet, and document. The data were analyzed by t-test. The conclusion of this research were science process skills was  significantly affected by Card Sort  with Mind Mapping  and  the application of  Card Sort  with Mind Mapping  has taken effect on student?s cognitive and psychomotor, affective achievement in studying biology of SMA N Banyudono Boyolali. Keywords : Card Sort with Mind Mapping  learning strategies, science process skills, biology student?s achievement